Climate Change, Climatic Extremes, and Human Societies in the Past - Lee, Harry F. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nowadays, more and more people realize the importance of global sustainability. Also, there has been an increasing number of quantitative studies investigating the connection between climate change and human societies in academia. Given this background, the Atmosphere Special Issue "Climate Change, Climatic Extremes, and Human Societies in the Past" aimed to highlight the major aspects of the climate-society nexus in ancient and recent human history. There are eight papers based on quantitative approaches to illustrate different forms of climate-society nexus in ancient, historical, and contemporary periods. Regarding ancient periods, the interconnection among climate, agriculture, and human societies is focused. Regarding historical periods, the non-linear and complex relationship between climate change and the positive checks (wars, famines, and epidemics) in historical China and pre-industrial Europe is revealed. Regarding contemporary periods, the papers focus on weather-related phenomena that significantly affect human societies. The complexity of those phenomena is also highlighted. The associated findings can help human societies to mitigate the adverse impacts of weather extremes better. This special issue contributes to the field of quantitative analysis of the climate-society nexus, both theoretically and methodologically, which could facilitate a more fruitful discussion about the climate-society nexus.